2023
DOI: 10.3390/plants12061248
|View full text |Cite
|
Sign up to set email alerts
|

Plant Species’ Capacity for Range Shifts at the Habitat and Geographic Scales: A Trade-Off-Based Framework

Abstract: Climate change is causing rapid shifts in the abiotic and biotic environmental conditions experienced by plant populations, but we lack generalizable frameworks for predicting the consequences for species. These changes may cause individuals to become poorly matched to their environments, potentially inducing shifts in the distributions of populations and altering species’ habitat and geographic ranges. We present a trade-off-based framework for understanding and predicting whether plant species may undergo ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 355 publications
0
4
0
Order By: Relevance
“…A majority of endangered tree species often occur in separate natural forests in the form of population. Previous researches have demonstrated that climate change may disrupt the existing species interactions because different species responds distinctively to climate change in phenological rhythm, physiological ecology, extinction risk, and potential distribution (Bellard et al, 2012;Ovaskainen et al, 2013;Vitasse et al, 2021;McNichol and Russo, 2023;Zurell et al, 2023). Therefore, we speculate that for a certain endangered species in different types of forest communities, the dominant tree species may have different responses to climate change.…”
Section: Introductionmentioning
confidence: 86%
“…A majority of endangered tree species often occur in separate natural forests in the form of population. Previous researches have demonstrated that climate change may disrupt the existing species interactions because different species responds distinctively to climate change in phenological rhythm, physiological ecology, extinction risk, and potential distribution (Bellard et al, 2012;Ovaskainen et al, 2013;Vitasse et al, 2021;McNichol and Russo, 2023;Zurell et al, 2023). Therefore, we speculate that for a certain endangered species in different types of forest communities, the dominant tree species may have different responses to climate change.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, it is critical to understand how GCC will impact different taxa in this biome (see Siyum, 2020). Empirical evidence and many model projections indicate that the populations of several taxa in the NSDF will hardly thrive under novel climatic conditions, and some will be condemned to local extinction (Hof et al., 2011; McNichol & Russo, 2023), most likely associated with relatively low tolerance to drought. In contrast, the colonization of new areas by species favored by the novel climatic conditions, including invasive and local species such as cacti, is also expected (Barreto Cavalcante & Praciano Sampaio, 2022; González‐M et al., 2019, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for forests, as they are critical providers of ecosystem services and regulators of climate from local to global scales (Anderson‐Teixeira et al., 2013 ; FAO & UNEP, 2020 ; Lawrence & Vandecar, 2015 ). Changes in climate regimes at large spatial scales are anticipated to shift the distribution of suitable environments for forests (Davis & Shaw, 2001 ; Hampe & Jump, 2011 ), likely causing some plant populations within a species' geographic range to become poorly matched to local conditions (McNichol & Russo, 2023 ). However, many forest plant species' ranges are projected to shift to higher latitudes or altitudes to track their climatic niche (Feeley et al., 2011 ; Skov & Svenning, 2004 ; Vellend et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%